Electroporative interleukin-10 gene transfer ameliorates carbon tetrachloride-induced murine liver fibrosis by MMP and TIMP modulation - Chou Wen-ying; Lu Cheng-nan; Lee Tsung-hsing; Wu Chia-ling; Hung Kung-sheng; Concejero Allan M; Jawan Bruno; Wang Cheng-haung (Acta Pharmacologica Sinica, 2016)
Aim: Liver fibrosis represents a process of healing and scarring in response to chronic liver injury. Effective therapies for liver fibrosis are lacking. Interleukin-10 (IL-10) is a cytokine that downregulates pro-inflammatory responses and has a modulatory effect on hepatic fibrogenesis. The aim of this study was to investigate whether electroporative IL-10 gene therapy has an hepatic fibrolytic effect on mice. Methods: Hepatic fibrosis was induced by administering carbon tetrachloride (CCl4) for 10 weeks in mice. The human IL-10 expression plasmid was delivered via electroporation after hepatic fibrosis was established. Histopathology, reverse transcription polymerase chain reaction (RT-PCR), immunoblotting, and gelatin zymography were used to investigate the possible mechanisms of action of IL-10. Results: Human IL-10 gene therapy reversed CCl4-induced liver fibrosis in mice. RT-PCR revealed that IL-10 gene therapy attenuated liver TGF-β1, collagen α1, fibronectin, and cell adhesion molecule mRNA upregulation. Following gene transfer, both the activation of α-smooth muscle actin and cyclooxygenase-2 were significantly attenuated. Furthermore, IL-10 significantly inhibited matrix metalloproteinase-2 (MMP-2) and tissue inhibitors of matrix metalloproteinase (TIMP) activation after CCl4 intoxication. Conclusions: We demonstrated that IL-10 gene therapy attenuated CCl4-induced liver fibrosis in mice. IL-10 prevented upregulated fibrogenic and pro-inflammatory gene responses. Its collagenolytic effect may be attributed to MMP and TIMP modulation. IL-10 gene therapy may be an effective therapeutic modality against liver fibrosis with potential clinical use.